(untitled) (Research, Society and Development, 2021)
The use of phytogenic additives in animal feed emerged with the need to replace traditional additives and growth promoters, which were banned for use by the European Union a few years ago and in Brazil recently. Since then, several works have been carried out for several species of animal production, so that currently the most used phytogenic additives are essential oils, extracts, herbs, spices and vegetable fractions that include bark, leaves, roots, seeds and others. These additives are composed of several bioactive substances of varied chemical nature, exerting positive functions on the animals’ organism. In rabbit farming, they are mainly used to improve the functioning of the digestive system, reduce sanitary challenge and promote greater nutrient digestibility. In addition to improving nutrition, consumption, stimulating digestion and performance, the use of bioactive substances reduces the incidence of diseases, improves reproductive parameters, acts as antifungals, anthelmintics, antivirals, antimicrobials, anticoccidials and antioxidants. Due to these benefits, the current review addresses different types of phytogenic compounds and bioactive substances used in rabbit production, focusing on reproduction, welfare and meat quality.